Wpływ wiedzy utajonej na czas trwania inwestycji budowlanej w warunkach transformacji - Buszko, Andrzej (The Secret Knowledge Impact on the Time Execution of Construction Projects during Transformation Period, 2006)
The aim of this paper is to set up the optimal conflict level that influences on secret knowledge. The study was conducted among 126 construction companies and the conflict between A ranked workers and site managers was elaborated. The best benefits regarded as the investment time shortening and budget savings were noted among all including "growth" companies the worst called "chaos" ones.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2006; nr 1121, s. 21-35